Study on Effect of Striatal mGluR2/3 in Alleviating Motor Dysfunction in Rat PD Model Treated by Exercise Therapy - Chen, Ping; Li, Xiaodong (Frontiers in Aging Neuroscience, 2019)
Background: Exercise therapy has been widely applied in clinical rehabilitation as an important practical and side effect—free adjuvant therapy, with a significant effect in alleviating motor dysfunction of patients with Parkinson’s disease (PD) or animal PD models. This study focuses on the effect of exercise therapy in reducing the concentration of extracellular glutamate (Glu) in the striatum in a rat PD model by upregulating the expression of group II metabotropic Glu receptor (mGluR2/3), so as to alleviate motor dysfunction in the rat PD model. Methods: Neurotoxin 6-hydroxydopamine (6-OHDA) was injected into the right medial forebrain bundle (MFB) of the rats to establish the semi-lateral cerebral damage PD model. The sham-operated group was given an equal amount of normal saline at the same site and taken as the control group. The apomorphine (APO)-induced rotational behavior test combined with immunohistochemical staining with tyrosine hydroxylase (TH) in the substantia nigra (SNc) and striatum was performed to assess the reliability of the model. The exercise group was given treadmill exercise intervention for 4 weeks (11 m/min, 30 min/day, 5 days/week) 1 week after the operation. The open field test (OFT) was performed to assess the locomotor activity of the rats; the Western blot technique was used to detect SNc TH and striatal mGluR2/3 protein expressions; real-time polymerase chain reaction (RT-PCR) was applied to detect striatal mGluR2 and mGluR3 mRNA expressions; the microdialysis—high-performance liquid chromatography (HPLC) method was adopted to detect the concentration of extracellular Glu in striatal neurons. Results: Compared with the control group, the number of rotations of each model group at the first week was significantly increased (P < 0.01); compared with the PD group, the number of rotations of the PD + exercise group at the third week and the fifth week was significantly decreased (P < 0.05, P < 0.01). Compared with the control group, the total movement distance, the total movement time, and the mean velocity of each model group at the first week were significantly reduced (P < 0.05); compared with the PD group, the total movement distance, the total movement time, and the mean velocity of the PD + exercise group at the third week and the fifth week were significantly increased (P < 0.01). Compared with the control group, the count of immunopositive cells and protein expression of SNc TH, and the content of immunopositive fiber terminals in the striatal TH of each model group significantly declined (P < 0.01). Compared with the PD group, the striatal mGluR2/3 protein expression of the PD + exercise group significantly rose (P < 0.01). Compared with the control group, the concentration of extracellular Glu in striatal neurons of each model group at the first week significantly grew (P < 0.05); compared with the PD group, the concentration of extracellular Glu in striatal neurons of the PD + exercise group at the third week and the fifth week was significantly decreased (P < 0.01); compared with the PD + exercise group, the concentration of extracellular Glu in striatal neurons of the group injected with mGluR2/3 antagonist (RS)-1-amino-5-phosphonoindan-1-carboxylic acid (APICA) into the striatum at the third week and the fifth week was significantly increased (P < 0.05, P < 0.01). Compared with the control group, the striatal mGluR2/3 protein expression of the PD group was significantly downregulated (P < 0.01); compared with the PD group, the striatal mGluR2/3 protein expression of the PD + exercise group was significantly upregulated (P < 0.05); compared with the control group, the striatal mGluR3 mRNA expression of the PD group was significantly downregulated (P < 0.01); compared with the PD group, the striatal mGluR3 mRNA expression of the PD + exercise group was significantly upregulated (P < 0.01); 6-OHDA damage and exercise intervention had no significant effect on the striatal mGluR2 mRNA expression (P > 0.05). Compared with the PD + exercise group, the total movement distance, the total movement time, and the mean velocity of the PD + exercise + APICA group were significantly decreased (P < 0.05); compared with the PD group, the PD + exercise + APICA group had no significant change in the total movement distance, the total movement time, and the mean velocity (P > 0.05). Conclusion: These data collectively demonstrate that the mGluR2/3-mediated glutamatergic transmission in the striatum is sensitive to dopamine (DA) depletion and may serve as a target of exercise intervention for mediating the therapeutic effect of exercise intervention in a rat model of PD.